The impact of diversity and educational backgrounds of executive boards on Indonesian bank performance - Putri, Arisma Solicha; Mandala, Eka; Harahap, Muhammad Farhan Hakim; Adinur, Reyhan Satria; Ahad, Sasi Waliyul; Hanggraeni, Dewi (University of Merdeka Malang, 2021)
This study identifies and analyzes the relationship between the diversity of the board of directors and the president director's educational background on the bank's financial performance. Based on 38 samples of Indonesian banks that have been listed on the Indonesia Stock Exchange. This study examines the static and dynamic relationship between the framework, which controls for the specific effects of each of the factors being tested. The results of this study indicate a significant influence and direction of negative correlation between gender diversity and citizenship diversity on bank financial performance. This study also shows a significant influence and direction of a positive correlation between the president director with an economic or business education background on the bank's financial performance. This study also discusses several managerial implications for banking companies and recommendations for the government in relation to the regulation of the board of directors of banks in Indonesia. DOI : https://doi.org/10.26905/jkdp.v25i2.5154